2019
DOI: 10.21009/segar/0801.05
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Latihan Plyometric Jump to Box Terhadap Power Otot Tungkai Pemain Bola Voli Pada Tim Putri Penjaskesrek Undana

Abstract: Rumusan masalah penelitian ini adalah: Apakah Ada Pengaruh Langsung Latihan Plyometric Jump To Box Terhadap Power Otot Tungkai Pemain Bola Voli Pada Tim Putri Penjaskesrek Undana?. Penelitian ini bertujuan untuk untuk mengetahui apakah dengan latihan plyometric jump to box dapat meningkatkan power otot tungkai pemain bola voli tim putri Penjaskesrek Undana. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian eksperimen, dimana suatu penelitian yang dilakukan secara ketat untuk mengetahui hub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
1
0
2
Order By: Relevance
“…However, the results of the post hoc test showed that there was a significant difference between the group given the combination treatment of plyometric and ladder drill exercises (Group TR and SH) and Fernandez-Fernandez et al, 2016;Filipas et al, 2023;Guo et al, 2021;Lu et al, 2022;Ozbar et al, 2014), as well as the ladder drill training program. The results of this study which stated that there were no significant differences in the TR (tuck jumpdouble leg run) and SH (squat jump-double leg hop) groups, were in line with several previous studies, even though the plyometric tuck jump and squat jump exercises were both can improve the performance of the physical condition of leg muscle power, but there is no known significant difference between the two (Ashari et al, 2019;Falah & Pranatahadi, 2019;Ratno & Darmawan, 2019). The previous study also revealed that the average value of increasing leg muscle power was more significant in the group that was given the plyometric tuck jump exercise intervention compared to the plyometric squat jump, although the significance value proved that there was no significant difference (Ashari et al, 2019;Falah & Pranatahadi, 2019;Ratno & Darmawan, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the results of the post hoc test showed that there was a significant difference between the group given the combination treatment of plyometric and ladder drill exercises (Group TR and SH) and Fernandez-Fernandez et al, 2016;Filipas et al, 2023;Guo et al, 2021;Lu et al, 2022;Ozbar et al, 2014), as well as the ladder drill training program. The results of this study which stated that there were no significant differences in the TR (tuck jumpdouble leg run) and SH (squat jump-double leg hop) groups, were in line with several previous studies, even though the plyometric tuck jump and squat jump exercises were both can improve the performance of the physical condition of leg muscle power, but there is no known significant difference between the two (Ashari et al, 2019;Falah & Pranatahadi, 2019;Ratno & Darmawan, 2019). The previous study also revealed that the average value of increasing leg muscle power was more significant in the group that was given the plyometric tuck jump exercise intervention compared to the plyometric squat jump, although the significance value proved that there was no significant difference (Ashari et al, 2019;Falah & Pranatahadi, 2019;Ratno & Darmawan, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study which stated that there were no significant differences in the TR (tuck jumpdouble leg run) and SH (squat jump-double leg hop) groups, were in line with several previous studies, even though the plyometric tuck jump and squat jump exercises were both can improve the performance of the physical condition of leg muscle power, but there is no known significant difference between the two (Ashari et al, 2019;Falah & Pranatahadi, 2019;Ratno & Darmawan, 2019). The previous study also revealed that the average value of increasing leg muscle power was more significant in the group that was given the plyometric tuck jump exercise intervention compared to the plyometric squat jump, although the significance value proved that there was no significant difference (Ashari et al, 2019;Falah & Pranatahadi, 2019;Ratno & Darmawan, 2019). This is because the motion in doing the plyometric tuck jump and ladder drill double leg run requires more explosive movements compared to the plyometric squat jump and ladder drill double leg hop.…”
Section: Discussionsupporting
confidence: 92%
“…Daya ledak otot tungkai penting dalam olahraga yang membutuhkan gerakan cepat dan mendadak seperti loncatan, lompatan, tolak, dan sprint (Wahyuni & Donie, 2020). Daya ledak otot tungkai sangat relevan dalam olahraga seperti bola voli, di mana kemampuan meloncat tinggi dan memukul bola dengan kuat memerlukan daya ledak yang baik (Arif & Alexander, 2019). Latihan daya ledak otot tungkai dapat mencakup berbagai metode seperti loncatan tunggal dan ganda serta latihan dengan beban yang sesuai.…”
Section: Kajian Teoriunclassified
“…In collecting data, it must also be accompanied by documentation, so that understanding of the main issues can be obtained (Arif & Alexander, 2019) The data obtained in this study will be analyzed using descriptive analysis. After all the data has been collected, the next step is to analyze the data so that a conclusion can be drawn.…”
Section: Documentationmentioning
confidence: 99%